Anodes for Carbon-Fueled Solid Oxide Fuel Cells - Zhou, W.; Jiao, Y.; Li, S.; Shao, Zongping (2016)
Solid oxide fuel cells (SOFCs) have been considered as one of the most promising technologies for high-efficiency electrical energy generation using a variety of fuels, including hydrogen, natural gas, biogas, carbon monoxide, liquid hydrocarbons and solid carbon. Carbon-fueled SOFCs (CF-SOFCs) potentially have the highest volume power density because solid carbon has a fuel energy density of 23.95 kWh L−1, which is approximately 10 times higher than that of liquid hydrogen. However, the reactivity and fluid mobility of carbon is significantly lower than those of gaseous fuels; thus, CF-SOFCs will be kinetically limited at the anode. Herein, we review the development of anodes in CF-SOFCs from the perspective of material compositions and microstructures. Challenges and research trends based on the fundamental understanding of the materials science and engineering for anode development in CF-SOFCs are discussed.